MODEL PEMBELAJARAN ” WEB BASED EDUCATION ” UNTUK MENINGKATKAN PRESTASI BELAJAR PENDIDIKAN KEWARGANEGARAAN DI KELAS XII IPA SMA NEGERI 1 GANTUNG - Sabarudin Sabarudin (Khazanah Pendidikan, 2015)
This study is an action of teachers to improve student learning achievement Civics Class XII Science SMAN 1 Gantung in the Academic Year 2014/2015. This classroom action research conducted in three cycles and includes four phases, namely planning, action, observation and reflection. Each action consists of three activities, namely the preliminary (appersepsi), the core activity of carrying out the Learning Model "Web Based Education", and cover with giving about evaluation, motivation and reinforcement. To assess learning achievement Civics, researchers used tools test instrument. The results showed that the use of the learning model "Web Based Education" can improve student achievement in high school civics class. This is evident from the learning achievement test data also showed an increase in pre-cycle that is as much as 7 students (20.59%) reached KKM with an average of 66.62, in the first cycle of students who achieve complete by 73.59% or 25 students with an average of 82.65 and the second cycle is equal to 88.24% or 30 students with an average of 90.24. After the whole cycle is done, it can be concluded that the use of Learning Model "Web Based Education" can improve learning achievement in civics class XII IPA SMAN 1 Gantung in the school year 2014/2015. Keywords: Web Based Education, Learning Achievement Civics